2021
DOI: 10.3390/pathogens10020219
|View full text |Cite
|
Sign up to set email alerts
|

Murine Typhus Infection in Pregnancy: Case Series and Literature Review

Abstract: Murine typhus is a flea-borne disease of worldwide distribution with a recent reemergence in the United States of America. There are limited data about the presentation, treatment, and outcomes in the pregnant population. We report on two cases of murine typhus during pregnancy and review the literature to compile previously reported cases. A comprehensive search was performed via the PubMed database for published articles between 1990 and 2020. Seven articles met the criteria of symptomatic pregnant murine ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The interactive illustration has been created using Tableau software (Version 2023) [15] and available from the link: https://bit.ly/fetal_outcome. This shows that most reports of scrub typhus are from Southeast Asia including 14 studies from India [3][4][5]16-26], 5 from Thailand [27][28][29][30][31] and 2 from Korea [32,33] and one each from Bhutan [34], Laos [13] and China [35] whereas the reports of other Rickettsia infections like murine typhus and Rocky Mountain spotted fever are more prevalent in USA [36][37][38][39][40]. On the other hand, there is no speci c geographical distribution of the cases of leptospirosis.…”
Section: Resultsmentioning
confidence: 99%
“…The interactive illustration has been created using Tableau software (Version 2023) [15] and available from the link: https://bit.ly/fetal_outcome. This shows that most reports of scrub typhus are from Southeast Asia including 14 studies from India [3][4][5]16-26], 5 from Thailand [27][28][29][30][31] and 2 from Korea [32,33] and one each from Bhutan [34], Laos [13] and China [35] whereas the reports of other Rickettsia infections like murine typhus and Rocky Mountain spotted fever are more prevalent in USA [36][37][38][39][40]. On the other hand, there is no speci c geographical distribution of the cases of leptospirosis.…”
Section: Resultsmentioning
confidence: 99%
“…However, ciprofloxacin failures have been reported [ 44 ]. Azithromycin has been primarily used to treat FBT during pregnancy [ 45 ], but a recent clinical trial clearly demonstrated the superiority of doxycycline over azithromycin in the treatment of FBT in terms of time to fever clearance and the frequency of treatment failure [ 46 ]. In the current study, case patient #2 failed to improve while on azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of doxycycline for rickettsioses in young children is endorsed by the American Academy of Pediatrics Committee on Infectious Diseases [159]. Most pregnant women with murine typhus have favorable outcomes, but poor neonatal outcomes from those with suboptimal treatment have been reported [163,164]. Doxycycline does not seem to be associated with the severe adverse events in pregnant women that have been reported with older tetracyclines [165,166].…”
Section: Treatment and Preventionmentioning
confidence: 99%